Design, Validation, and Reliability of a Basketball Skill and Performance Test Instrument in Adolescent Players - Muhammad Irvan Eva Salafi; Wawan Sundawan Suherman; Bernadeta Suhartini; Muhammad Sigit Antoni; Kukuh Wahyudin Pratama; Risti Nurfadhila; Wisnu Nugroho; Yulvia Miftachurohmah (OVS LLC, 2023)
Study purpose. The assessment tools or skills tests, such as the AAHPERD basketball skill test and the Johnson basketball test, are all partial or separate. All these tests are old products, while the game of basketball is constantly evolving. The purpose of this study was to design and validate basketball skills and performance tests for players aged 14-16 years to shorten the test time, shorten the waiting time for results, and be comprehensive so that they can reflect real abilities and can be used as a reference when carrying out selection and evaluation. Materials and methods. A total of 7 experts assessed the 11 elements (86 items) of the basketball skill and performance test (BSPT). Three academic experts and four basketball coach experts took part in the study. Data was collected using the Delphi technique and test-retest, and data was analyzed using Aiken's formula, intraclass correlation coefficients (ICC), and Cronbach's alpha. Results. With a value of 0.91, the expert assessment tool shows that the content validity of the aspect is good. Cronbach's alpha was used to measure the reliability of every aspect of the basketball skill and performance test instrument, and the results were 0.918. The result of the ICC score agreement between raters is 0.912, while for one rater, the consistency is 0.596. Conclusions. The implications of this study could prove that the BSPT can be used to assess the skill level of adolescent basketball players, benefiting not only basketball coaches but also physical education teachers.